How m6A sneaks into DNA - Spingardi, P; Kriaucionis, S (Nature Research, 2020)
The biological function and origin of m6A in DNA have been widely debated. A new study demonstrates that the majority of m6A in DNA originates from RNA catabolism via a nucleotide salvage pathway.